2020
DOI: 10.1038/s41467-020-15116-z
|View full text |Cite
|
Sign up to set email alerts
|

Structured graphene metamaterial selective absorbers for high efficiency and omnidirectional solar thermal energy conversion

Abstract: An ideal solar-thermal absorber requires efficient selective absorption with a tunable bandwidth, excellent thermal conductivity and stability, and a simple structure for effective solar thermal energy conversion. Despite various solar absorbers having been demonstrated, these conditions are challenging to achieve simultaneously using conventional materials and structures. Here, we propose and demonstrate three-dimensional structured graphene metamaterial (SGM) that takes advantages of wavelength selectivity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
273
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 358 publications
(274 citation statements)
references
References 44 publications
0
273
0
1
Order By: Relevance
“…No significant change was observed, and the measured output SPM spectra in Figure 6 were repeatable when we reinjected the optical pulses, indicating that the optically induced changes (e.g., loss, n2) of the GO films were not permanent. Note that we previously showed that the material properties of GO can also be permanently changed by femtosecond laser pulses [38][39][40][41] with significantly higher peak powers. This is distinct from the reversible power-dependent changes observed here.…”
Section: Kerr Nonlinearity (N2) Of the Go Filmsmentioning
confidence: 92%
See 1 more Smart Citation
“…No significant change was observed, and the measured output SPM spectra in Figure 6 were repeatable when we reinjected the optical pulses, indicating that the optically induced changes (e.g., loss, n2) of the GO films were not permanent. Note that we previously showed that the material properties of GO can also be permanently changed by femtosecond laser pulses [38][39][40][41] with significantly higher peak powers. This is distinct from the reversible power-dependent changes observed here.…”
Section: Kerr Nonlinearity (N2) Of the Go Filmsmentioning
confidence: 92%
“…Among the various 2D materials, GO has received increasing interest due to its ease of preparation as well as the tunability of its material properties [36][37][38][39][40][41]. Previously, we reported GO films with a giant Kerr nonlinearity of about 4 orders of magnitude higher than that of silicon [40,42], and demonstrated significantly enhanced four-wave mixing (FWM) in doped silica waveguides and microring resonators integrated with layered GO films [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafast direct laser writing (DLW) has been widely used as a laser reduction method that is capable of both 2D and 3D writing of arbitrary patterns [41][42][43][44][45][46][47][48]. Ultrashort laser pulses offer low thermal effects that enable high fabrication resolution as well as rich light-matter interaction mechanisms and dynamics.…”
Section: Large and Tunable Optical Bandgapmentioning
confidence: 99%
“…The strong light absorption in thin films with a large surface area and the very broad spectral / angular responses are highly desirable for solar thermal applications. A solar-thermal absorber based on 3D structured rGO was reported subsequently [44],…”
Section: Light Absorbersmentioning
confidence: 99%
See 1 more Smart Citation